Prevailing Aesthetic Morals Philosophy In College of Physical Education and Sport Sciences In The University of Mosel - Abdul Ilah, Alaa (Journal of Physical Education, 2019)
Prevailing Aesthetic Morals Philosophy In College of Physical Education and Sport Sciences In The University of MoselThe research aimed at identifying the philosophy of aesthetic morals prevailing in the college of physical education and sport sciences in the University of Mosel. The researcher hypothesized that the students have a high level of aesthetic morals as well as they have different level of morals in different fields. The researcher used a questioner to collect the data from the subjects that were physical education and sport sciences students in the University of Mosel. The data was collected and treated using proper statistical operations to conclude that the subject have a good level of athletic morals.